HUBUNGAN BERAT BEBAN, FREKUENSI ANGKAT, POSTUR KERJA DENGAN KELUHAN THORACIC OUTLET SYNDROME PADA PENAMBANG PASIR TRADISIONAL DESA BANJARPARAKAN - Sinta Mahestri; Siswi Jayanti; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2021)
Thoracic outlet syndrome (TOS) is a constellation of symptoms caused by compression of nerve and blood vessel between the first rib and clavicle that can cause pain, numbness or tingling, early fatigue, cold fingers and bluish color. In doing their job, sand miners often lift heavy load with poor postures,repetitive movement that will cause local mechanical stress which can result in thoracic outlet syndrome.  The purpose of this study was to analyze the relation between weight of load, lifting frequency, work posture with thoracic outlet syndrome complaints in the traditional sand miners of Banjarparakan Village. This study was a quantitative research with cross sectional study approach. The sample was the entire population of 33 traditional sand miners in Banjarparakan Village. This study using Roos Test to find out incidence of Thoracic Outlet Syndrome (TOS), floor scale to measure weight of load, and Rapid Upper Limb Assessment (RULA) to measure work posture. Based on statistical test using Fisher Exact, there was association between weight of load (p-value = 0,005), lifting frequency (p-value = 0,016), and lifting activity work posture (p-value = 0,036) with thoracic outlet syndrome complaints and there was no relation between pouring activity work posture (p-value = 0,257) with thoracic outlet syndrome complaints. The traditional sand miners should stretch before and interrupted during their work.